Are crises good for long-term growth? The role of political institutions - Alberto F. Cavallo; Eduardo A. Cavallo (Inter-American Development Bank, Research Department, 2008)
This paper provides empirical evidence for the importance of institutions in determining the outcome of crises on long-term growth. Once unobserved country-specific effects and other sources of endogeneity are accounted for, political institutions affect growth through their interaction with crises. The results suggest that only countries with strong democracies, high levels of political competition and external constraints on government can potentially benefit from crises and use them as opportunities to enhance long-term output per capita and productivity growth.
Keywords: O40; O43; F43; 330; financial crises; democracy; political institutions; economic growth; Finanzmarktkrise; Demokratie; Institutionalismus; Wirtschaftswachstum; Welt